Periodontal status at two years of follow-up in patients with Newly Diagnosis of type 2 Diabetes Mellitus - Arely Saindaleth López Reyes; Eder Patiño-Rivera; Ana Cristina García-Ulloa; Sergio Hernández-Jiménez; For the Group of Study CAIPaDi (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2019)
Background: Diabetes increases the risk of periodontal disease. Integrating periodontal care with the treatment of type 2 diabetes (T2DM) may facilitate the management of both diseases. Aim of the study: To evaluate the periodontal status at two years in patients with T2DM and assess glycated hemoglobin (HbA1c) according to the severity and extension of periodontitis. Methods: This is a descriptive cohort study. Full-mouth periodontal evaluation was performed and blood samples were obtained to analyze HbA1c at baseline, 3, 12 and 24 months. Clinical attachment level, probing depth, bleeding on probing and oral hygiene were measured. We analyzed mean HbA1c according to severity and extension of periodontitis. Results: We included 160 patients with T2DM. Basal HbA1c was 7.7 ± 2.2%. Periodontal health increased 27.5 % at 24 months. At baseline, moderate and severe periodontitis was present in 29.9% and 13.4% patients, respectively. At two years, 22.5% and 11.8% had moderate and severe periodontitis, respectively. Bleeding on probing decreased from 15.7% to 6.4% at 24 months. HbA1c was higher in subjects with severe and generalized periodontitis. Conclusions: The periodontal status in patients with newly diagnosis of T2DM who received a comprehensive diabetes care improved at 3 months. This improvement was maintained at 24 months of follow-up.